PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA JASA TRANSPORTASI OJEK ONLINE (Studi Kasus Pada Konsumen Gojek Malang) - Dwi Danesty Deccasari (Politeknik Negeri Malang, 2018)
The purpose of this research is to analyze the extent of Customer Satisfaction variables are able to improve Service Quality significantly to Customer Loyalty to consumers in Malang. The population in this study are customers who have used online transportation service Gojek in Malang. The sampling technique used in the research is using non probabilitysampling method with sampling method that used is accidental sampling. From the result of path analysis in the above table, it can be concluded that the influence of the service quality on customer satisfaction (Y1) of 79.5%. This means that from the five dimensions of service quality, dimensions that further affect customer satisfaction is the dimension of reliability, responsiveness, and empathy.Based on the result of determination test (R²) = 0,722 known that variable of service quality and customer satisfaction variable able to contribute 72.2% to customer loyalty.